2018
DOI: 10.13005/ojc/340242
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Isolated from Horseshoe Crab Tachypleus gigas from the Malay Peninsula

Abstract: Chitosan that was isolated from horseshoe crabs, Tachypleus gigas, for this study were from estuary area in Balok Pahang (East coast) and Muar Johor (West coast) of the Malay Peninsula. The isolation of chitosan was carried out by chemical processes involving deproteinization, demineralization and deacetylation. Physicochemical properties and antibacterial activity were analysed to determine its potential commercialization. The degree of deacetylation (DD) was higher for samples from Balok than Muar (42.4% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…(Edgecombe and Legg, 2014;Giribet, 2018). Kassim et al (2018) reported that horseshoe crabs (Carcinoscorpius rotundicauda) have a bodyforming and protective shell with a strong elastic structure. It is formed by the evolutionary process of the hardened material (Joffe et al, 1975).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Edgecombe and Legg, 2014;Giribet, 2018). Kassim et al (2018) reported that horseshoe crabs (Carcinoscorpius rotundicauda) have a bodyforming and protective shell with a strong elastic structure. It is formed by the evolutionary process of the hardened material (Joffe et al, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (2008a) described that a shell of horseshoe crabs consists of 50-60 nm chitin fibers arranged in parallel and layers (nanofibers of chitosan layers). Characteristics of functional groups in the shells of horseshoe crabs show that the shells consist of hydroxyl groups, secondary amides, asymmetric C-H, C-H alkanes, C=O secondary amides and C-aliphatic ether (Kassim et al, 2018). Briefly, the arthropods exoskeleton consists mainly of chitin and is multifunctional, such as supporting the body, resisting mechanical loads, protecting harsh environmental conditions and resistance to desiccation (Neville, 1975;Vincent, 1991Vincent, , 2002Vincent and Wegst, 2004;Sanchez et al, 2005;Meyers et al, 2008).…”
Section: Introductionmentioning
confidence: 99%